2020
DOI: 10.3390/ijerph17030945
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Transportation Modes and Time among Chinese Population from 2002 to 2012

Abstract: Giving the rising trends in obesity and chronic diseases in China, strategies to increase physical activity are important. Transport-related activity is a substantial source of physical activity and can be easily incorporated into the daily lives. It is a key social factor of health, which can help improve people’s mental and physical health and decrease environmental pollution. However, little is known about recent trends in transportation modes and time in China. Between 2002 and 2010–2012, information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
(41 reference statements)
2
8
1
Order By: Relevance
“…The results show a 36.5% prevalence of AC to school. These results are similar to the 37.5% of Brazilian adolescents [ 43 ] but lower than the 54.3% of the Chinese adolescents [ 18 ]. At the national level, these results are in line with those of previous Portuguese HBSC studies (e.g., 35% in Loureiro et al [ 44 ]).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results show a 36.5% prevalence of AC to school. These results are similar to the 37.5% of Brazilian adolescents [ 43 ] but lower than the 54.3% of the Chinese adolescents [ 18 ]. At the national level, these results are in line with those of previous Portuguese HBSC studies (e.g., 35% in Loureiro et al [ 44 ]).…”
Section: Discussionsupporting
confidence: 81%
“…However, the prevalence of AC is low and seems to be decreasing in the last decades in several countries. For example, it decreased in China from 83.8% in 2002 to 54.3% in 2012 [ 18 ] and from 48% in 1969 to 13% in 2009 in the USA [ 19 ], with similar results in other developed countries such as Canada [ 20 ], Australia [ 21 ], Ireland [ 22 ], Spain [ 23 ], and Portugal [ 24 ].…”
Section: Introductionmentioning
confidence: 86%
“…Active transportation decreased the risk of overweight/obesity in men but not in women. According to the research of Gong et al [18], female travel time was shorter than that of males. This may be due to insufficient walking/cycling intensity or distances, i.e., not enough to prevent obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of occupation activity has been significantly reduced by scientific and technological progress, and >60% of Chinese occupational populations work with light occupation activity intensity which lead to less physical activity [17]. More and more, private cars, subways, and buses have made transportation more convenient [18]. The widespread availability of entertainment devices such as televisions, computers, and smartphones have increased sedentary behavior [19].…”
Section: Introductionmentioning
confidence: 99%
“…The people with a high socioeconomic status also were more likely to travel using transportation that lacked PA, such as private cars, taxis, motorcycles, etc. [ 37 ]. Research also showed that the family per capita annual income was positively correlated with obesity in China [ 38 ].…”
Section: Discussionmentioning
confidence: 99%